Soy Protein Diet Improves Nutritional Status of Offspring with Intrauterine Growth Restriction: A Scoping Review - Rimonta F Gunanegara; Rafhani Rosyidah; Agung Dewanto; Sunarti Sunarti (Journal of Medicine and Health, 2023)
The intake of a low-protein diet during pregnancy can lead to alteration of fetal programming with long-term postnatal consequences exposing offspring with malnutrition to metabolic syndrome in adulthood. Accordingly, a more affordable alternative source of protein, such as soy, is used to improve nutrition. The objective of this study was to examine the advantages and disadvantages of soy as an alternative protein source to improve offspring nutrition with Intrauterine Growth Restriction (IUGR). The method used was a scoping review, and the design was selected to provide coverage on a certain topic with the concepts from available literature. Systematic searches were performed in six databases: PubMed, EBSCO, ScienceDirect, SCOPUS, Sage Journals, and Cochrane Library. Data collection included reports published from January 2013 to January 2023. Nine articles meeting the inclusion criteria were obtained and analyzed for review. Protein from a plant source is considered a good alternative in restoring nutrition to malnourished offspring in early life. Furthermore, the dietary deficiency of soy can be corrected with close monitoring. As a conclusion, the quality of life of offspring with IUGR is improved through a well-planned supplementation.